Computational assessment of effects of throat diameter on combustion and turbulence characteristics in a pre-chamber engine. (25th July 2022) - Silva, Mickael; Liu, Xinlei; Hlaing, Ponnya; Sanal, Sangeeth; Cenker, Emre; Chang, Junseok; Johansson, Bengt; Im, Hong G.
Graphical abstract: Highlights: Narrow throat influences field variables at spark timing within the pre-chamber. The pre-chamber throat affects the turbulence levels which enhances the combustion. Throat diameter influences the flow inside the pre-chamber, which can lead to choking. The pre-chamber design should avoid premature interaction with the piston walls. The piston is responsible for the majority of wall heat losses due to jet impingement. Abstract: Towards fundamental investigation of key physical aspects of pre-chamber combustion, the current work utilizes computational fluid dynamics to comprehend the effect of the throat diameter in an engine operated with methane. Previous studies showed that this parameter is dominant in pressure build-up and flow pattern inside the pre-chamber, suggesting that a detailed characterization is necessary. This pre-chamber type is composed of an upper conical part that lodges the spark plug and fuel injector, followed by a straight and tubular region called throat, which tip accommodates the nozzles responsible for the charge exchange between pre and main chambers. Two types of pre-chamber having distinct throat diameters are investigated, while utilizing consistent experimental data for validation of the model. The combustion process is modeled with the G-Equation model; the laminar flame speed was tabulated from a methane oxidation mechanism reduced from the GRI 3.0; the turbulent flame speed was computed using Peters' relation. The simulations were run for a full cycle, starting at exhaust valve opening. A homogeneous charge of methane is considered at the intake port, maintaining a global λ = 1.8, while 3% of total energy fuel is added through the pre-chamber. The results show that the throat changes the flow field inside the pre-chamber, impacts the air-fuel ratio, stratification, turbulence, jet dynamics, and ultimately the pre and main chambers combustion processes and heat fluxes. The combustion regime according to the Borghi-Peters diagram were found to lay in the thin reaction zone and in the flamelet regime.